2012
DOI: 10.14569/ijacsa.2012.030410
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of OpenMP & OpenCL Parallel Processing Technologies

Abstract: Abstract-This paper presents a comparison of OpenMP andOpenCL based on the parallel implementation of algorithms from various fields of computer applications. The focus of our study is on the performance of benchmark comparing OpenMP and OpenCL. We observed that OpenCL programming model is a good option for mapping threads on different processing cores. Balancing all available cores and allocating sufficient amount of work among all computing units, can lead to improved performance. In our simulation, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…A vendor-specific compiler is employed to optimize OpenCL to the target architecture. Previous studies (such as [11,35]) have shown that implementations with OpenCL achieve very close performance to those with native languages such as CUDA and OpenMP on the GPU and the CPU, respectively.…”
Section: Openclmentioning
confidence: 95%
“…A vendor-specific compiler is employed to optimize OpenCL to the target architecture. Previous studies (such as [11,35]) have shown that implementations with OpenCL achieve very close performance to those with native languages such as CUDA and OpenMP on the GPU and the CPU, respectively.…”
Section: Openclmentioning
confidence: 95%
“…OpenCL programs can be coded once and run on any OpenCL-compatible devices. Existing studies [11,34] have shown that programs in OpenCL can achieve very close performance to those in platform-specific languages such as CUDA for NVIDIA GPUs and OpenMP for CPUs. For example, Fang et al [11] demonstrate that the CUDA-based implementations are at most 30% better than OpenCL-based implementations on NVIDIA GPUs.…”
Section: Unified Programming Interfacementioning
confidence: 99%
“…For example, Fang et al [11] demonstrate that the CUDA-based implementations are at most 30% better than OpenCL-based implementations on NVIDIA GPUs. On CPUs, OpenCL even outperforms OpenMP in many scenarios [34].…”
Section: Unified Programming Interfacementioning
confidence: 99%
“…A demanding need to increase the computational performance in science and engineering headed for heterogeneous computing and highly parallel architectures thus created a strong need for programmers to develop infrastructure in the form of libraries routine to support computing is heterogeneous hardware platforms [9]. Faster executions of public key cryptography and precisely RSA are currently of extreme importance.…”
Section: Figure 1 the Different Architecture Cpu Vs Gpu [7]mentioning
confidence: 99%